Extraction of Essential Oil from Cloves (Syzygium aromaticum) Using Ultrasound Microwave Assisted Extraction Method: Ekstraksi Minyak Atsiri dari Cengkeh (Syzygium aromaticum) Menggunakan Metode Ekstraksi Berbantuan Gelombang Mikro Ultrasonik - Dwi Nur Arinal Khaq; Annisa Rachma Meydyanti; Erliyanti, Nove Kartika (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2024)
Ultrasound Microwave Assisted Extraction (UMAE) is an alternative to extracting clove essential oil by combining ultrasonic waves and microwaves to improve the efficiency and effectiveness of extraction. The purpose of this study is to examine the effect of microwave power and extraction time on the yield and density of clove essential oil. The cloves are reduced to a size of ± 0.5 cm and then dried using an oven for 60 minutes at a temperature of 70 °C. The pre-treatment process is carried out for 5 minutes with a temperature of 40 °C assisted by ultrasonic waves. After the pre-treatment process, the results obtained were then further extracted with microwave assistance with variable extraction times of 30, 40, 50, 60, and 70 minutes and microwave power of 150, 300, 450, and 600 Watts. The results showed that the addition of microwave power and extraction time had a significant influence on the yield value and density of clove essential oil. The best results of clove essential oil extraction using the Ultrasound Microwave Assisted Extraction method were obtained at 600-watt microwave power and at 70 minutes of extraction time with a yield value of 10.63% and a density of 1.0515 gr/ml.